The combination treatment of cholesterol‐loaded methyl‐β‐cyclodextrin and methyl‐β‐cyclodextrin significantly improves the fertilization capacity of vitrified bovine oocytes by protecting fertilization protein JUNO. Issue 3 (18th January 2021) - Hao, Tong; Zhang, Peipei; Hao, Haisheng; Du, Weihua; Pang, Yunwei; Zhao, Shanjiang; Zou, Huiying; Zhu, Huabin; Yu, Weili; Li, Shujing; Zhao, Xueming
Abstract: Many experiments show that vitrification significantly reduces the fertilization capacity of mammalian oocytes, restricting the application of vitrified oocytes. It has been proven that the JUNO protein plays a vital role in mammalian oocytes fertilization. However, little information is available about the effects of vitrification on the JUNO protein and the procedure to protect it in bovine oocytes. Here, the present study was designed to investigate the effect of vitrification on the JUNO protein level in bovine oocytes. In this study, MII oocytes were treated with cholesterol‐loaded methyl‐β‐cyclodextrin (CLC; 0, 10, 15, 20 mM) for 45 min before vitrification and methyl‐β‐cyclodextrin (MβCD; 0, 2.25, 4.25, 6.25 mM) for 45 min after thawing (38–39°C). Then, the expression level and function of JUNO protein, cholesterol level in the membrane, the externalization of phosphatidylserine, sperm binding capacity and the developmental ability of vitrified bovine oocytes were examined. Our results showed that vitrification significantly decreased the JUNO protein level, cholesterol level, sperm binding capacity, development ability, and increased the promoter methylation level of the JUNO gene and apoptosis level of bovine oocytes. Furthermore, 15 mM CLC + 4.25 mM MβCD treatment significantly improved the cholesterol level and increased sperm binding and development ability of vitrified bovine oocytes. In conclusion, the combination treatment of cholesterol‐loaded methyl‐β‐cyclodextrin and methyl‐β‐cyclodextrin significantly improves the fertilization capacity of vitrified bovine oocytes by protecting fertilization protein JUNO.